PENGARUH BANTUAN SOSIAL, TINGKAT PENDIDIKAN DAN TINGKAT PENGANGGURAN TERBUKA (TPT) TERHADAP KEMISKINAN DI INDONESIA TAHUN 2018-2022 DALAM PERSPEKTIF EKONOMI ISLAM - Aliyah, Tsabitah; Bahtiar , Muhammad Yusuf; Zulaikah (Cattleya Darmaya Fortuna, 2025)
One of the goals of the state in carrying out development is to realize social welfare. However, in the development process, there are still problems faced, one of which is the issue of poverty. Poverty is defined as a person's inability to meet the basic needs of life. It is also still a problem in Indonesia because, in the last 5 years (2018-2022), the poverty rate has fluctuated every year and in every province, with the highest poverty occurring in 2021. The purpose of this study is to examine the effects of social assistance, education level, and the open unemployment rate. In this study, the sample determination method utilized the purposive sampling technique. The sample spans the last 5 years, namely 2018-2022, from data on the poor population, data on the realization of the APBD subsection of social assistance spending, data on the average length of schooling, and data on the open unemployment rate from 34 provinces in Indonesia. The data analysis technique used in this study is panel data regression analysis with Eviews 13 software. Based on the results of the study, it is stated that social assistance has a positive and significant effect on poverty in Indonesia from 2018 to 2022. The level of education has a negative and insignificant effect on poverty in Indonesia during the same period. The open unemployment rate has a positive and insignificant effect on poverty in Indonesia from 2018 to 2022. Meanwhile, social assistance, education level, and the open unemployment rate simultaneously affect poverty in Indonesia from 2018 to 2022.